Novel uncertainty principles concerning linear canonical wavelet transform - Mawardi Bahri; Samsul Ariffin Abdul Karim (Multidisciplinary Digital Publishing Institute (MDPI), 2022)
The linear canonical wavelet transform is a nontrivial generalization of the classical wavelet transform in the context of the linear canonical transform. In this article, we first present a direct interaction between the linear canonical transform and Fourier transform to obtain the generalization of the uncertainty principles related to the linear canonical transform. We develop these principles for constructing some uncertainty principles concerning the linear canonical wavelet transform.